2013
DOI: 10.1109/led.2013.2260820
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of ${\rm HfO}_{2}/{\rm SrTiO}_{3}$ Hetero-Oxide Transistors Using Argon Bombardment

Abstract: An effective interface engineering method is developed to improve performance of SrTiO 3 -based hetero-oxide transistors. HfO 2 /SrTiO 3 hetero-oxide transistors made on argon ions bombarded SrTiO 3 surfaces show eight times increase in drive currents and more than five times increase in mobility when compared with the un-bombarded HfO 2 /SrTiO 3 transistors. The improvement is attributed to the Fermi-level shift as the results of the bombardment. These HfO 2 /SrTiO 3 -based nMOSFETs show field-effect electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In [8], we reported that by 45-s argon bombardment, the drive currents of HfO 2 /SrTiO 3 device were increased by about eight times, accompanied with more than five times increase in the field-effect mobility, but the mechanism is not clear. In above, it is shown that the performance of HfO 2 /SrTiO 3 device can be much improved by reducing interface traps.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [8], we reported that by 45-s argon bombardment, the drive currents of HfO 2 /SrTiO 3 device were increased by about eight times, accompanied with more than five times increase in the field-effect mobility, but the mechanism is not clear. In above, it is shown that the performance of HfO 2 /SrTiO 3 device can be much improved by reducing interface traps.…”
Section: Resultsmentioning
confidence: 99%
“…It may be more proper to calibrate E S for each device, but it will not affect our conclusion. In addition, the effective mobility is set to 4 cm 2 /Vs, which is based on the experimental data [8]. As shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations